Reception and Poetics in Keats - Robinson, J. author. aut Link
XIV, 205 p.
Keywords: Occasioned by the spirit of celebrating Keats's 200th birthday (31 October 1995), Jeffrey C. Robinson's Reception and Poetics in Keats offers at once a history and readings of the many praise and commemorative poems to or about Keats (collected in an appendix) from the time of his early death up to the present day and a consequent rethinking of Keats's own poems and poetics. Keats emerges as a poet uniquely available and useful to the experimental poets of our own time.